Development and Performance Evaluation of a Low-Cost, Energy-Efficient Air Fryer Prototype Using Incandescent Bulb Heating for Oil-Free Food Processing - Lamaega, Jolanda Ch. E.; Paat, Frangky J.; Sintaro, Sanriomi Sintaro; Saroinsong, Denny (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2026)
Oil-free cooking technologies are increasingly important for promoting healthier diets, reducing dependency on volatile oil markets, and enabling sustainable food processing—particularly in rural and resource-constrained environments. This study presents the design and evaluation of a low-cost air fryer prototype powered by incandescent bulbs (60–150 W), constructed using locally available materials. Thermal performance testing showed that the prototype achieved stable chamber temperatures up to 115 °C, enabling effective oil-free frying of potato slices, banana slices, and chicken nuggets. Frying performance, measured through cooking time, moisture reduction, and sensory evaluation, demonstrated acceptable product quality with significant energy savings: only 25–75 Wh per cycle, roughly one-tenth the energy use of conventional commercial air fryers. The prototype also offers potential as a multifunctional device for dehydration and defrosting, supporting broader postharvest applications in smallholder agritech. These results highlight a promising pathway for low-power, low-cost, and sustainable food processing technologies suitable for deployment in rural communities. Future work will focus on optimizing performance, expanding product capabilities, and validating user acceptance in real-world agritech settings. Keywords: Low-power Air fryer, incandescent bulb heating, oil-free cooking, energy-efficient food processing, sustainable technology.